2017
DOI: 10.1016/j.bbadis.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Acid Ceramidase Deficiency is characterized by a unique plasma cytokine and ceramide profile that is altered by therapy

Abstract: Acid Ceramidase Deficiency (Farber disease, FD) is an ultra-rare Lysosomal Storage Disorder that is poorly understood and often misdiagnosed as Juvenile Idiopathic Arthritis (JIA). Hallmarks of FD are accumulation of ceramides, widespread macrophage infiltration, splenomegaly, and lymphocytosis. The cytokines involved in this abnormal hematopoietic state are unknown. There are dozens of ceramide species and derivatives, but the specific ones that accumulate in FD have not been investigated. We used a multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 33 publications
3
46
1
Order By: Relevance
“…Previous studies by other groups have indicated that neither the acid ceramidase subtype (30), nor the neutral ceramidase subtype (31) contributes to blood SPH and S1P formation. Our previous study demonstrated that the alkaline ceramidase family is important for the maintenance of high blood levels of S1P in mice (32), but which member in the alkaline ceramidase family plays such a role was unknown.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies by other groups have indicated that neither the acid ceramidase subtype (30), nor the neutral ceramidase subtype (31) contributes to blood SPH and S1P formation. Our previous study demonstrated that the alkaline ceramidase family is important for the maintenance of high blood levels of S1P in mice (32), but which member in the alkaline ceramidase family plays such a role was unknown.…”
Section: Discussionmentioning
confidence: 92%
“…These studies suggest that, in the alkaline ceramidase family, ACER2 is the only member that plays a role in maintaining high blood levels of S1P in mice via the generation of its precursor, SPH. Previous studies have shown that knocking out Asah1 (30) or Asah2 (31) does not alter blood SPH and S1P levels in mice, and it remains unclear whether the lack of change in the blood levels of SPH and S1P in Asah1‐ or Asah2 ‐deficient mice is a result of a compensatory effect by ACER2. If not, the remainder of the blood S1P precursor, SPH, in Acer2 −/− mice either comes from diet or is generated via an unidentified metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite phenotype of ceramidase KO models in intestinal inflammation is likely a result of different cellular and tissue localization that regulate different pools of ceramide (25). Although AC has been implicated in immune regulation in cellular and animal models, its function in intestinal inflammation has not yet been investigated (28, 29, 31, 32). In this study, we demonstrate elevated expression of AC in colitis and in murine DSS‐induced colitis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we initially find increased levels of AC expression in the colon lamina propria of human and murine colitis tissue. Because cellular models have demonstrated a role for AC in immune processes and cancer (28)(29)(30)(31)(32)(33), we generated a myeloidspecific KO model of AC to investigate the role of the enzyme in intestinal inflammation using the model of dextran sulfate sodium (DSS)-induced colitis. In this study, we demonstrate a novel role for AC in the myeloid compartment that regulates the threshold of neutrophil recruitment and the production of inflammatory cytokines in the colon.…”
mentioning
confidence: 99%